Predictors of Postpartum Persisting Hypertension Among Women with Preeclampsia Admitted at Carlos Manuel de Cèspedes Teaching Hospital, Cuba - Fajardo Tornes Y; Nápoles Mèndez D; Alvarez Aliaga A; Santson Ayebare D; Ssebuufu R; Byonanuwe S (Dove Medical Press, 2020)
Yarine Fajardo Tornes,1,2 Danilo Nápoles Mèndez,3 Alexis Alvarez Aliaga,4 David Santson Ayebare,5 Robinson Ssebuufu,6 Simon Byonanuwe2 1Department of Obstetrics and Gynaecology, Granma University of Medical Sciences, Bayamo, Cuba; 2Department of Obstetrics and Gynaecology, Kampala International University Western Campus, Bushenyi, Uganda; 3Department of Obstetrics and Gynaecology, Santiago de Cuba University of Medical Sciences, Santiago de Cuba, Cuba; 4Department of Internal Medicine, Granma University of Medical Sciences, Bayamo, Cuba; 5Interdisciplinary Research & Development Center Limited, Mbarara, Uganda; 6Department of Surgery, Kampala International University Western Campus, Bushenyi, UgandaCorrespondence: Simon ByonanuweDepartment of Obstetrics and Gynaecology, Kampala International University Western Campus, P. O. Box 71, Bushenyi, UgandaTel +256 775 730088Email byonsimon@gmail.comPurpose: We established the prevalence and predictors of persisting hypertension in women with preeclampsia admitted at the Carlos Manuel de Cèspedes Teaching Hospital in Cuba so as to guide the health-care providers in early identification of the patients at risk for timely intervention.Patients and Methods: A three-year prospective cohort study was conducted between March 2017 and March 2020. A cohort of 178 women diagnosed with preeclampsia at the hypertension unit of Carlos Manuel de Cèspedes Teaching Hospital were recruited. Interviewer administered questionnaires and laboratory and ultrasound scan result forms were used to collect the data. Binary logistic regression was conducted to determine the predictors. All data analyses were conducted using STATA version 14.2.Results: Forty-five (27.8%) of the studied 162 patients were still hypertensive at 12 weeks postpartum. Maternal age of 35 years or more (aRR=1.14,95% CI:1.131– 4.847, p=0.022), early onset preeclampsia (before 34 weeks of gestation) (aRR=7.93, 95% CI:1.812– 34.684, p=0.006), and elevated serum creatinine levels of more than 0.8mg/dl (aRR=1.35, 95% CI:1.241– 3.606, p=0.032) were the independent predictors of persisting hypertension at 12 weeks postpartum.Conclusion: Recognition of these predictors and close follow-up of patients with preeclampsia will improve the ability to diagnose and monitor women likely to develop persisting hypertension before its onset for timely interventions.Keywords: persisting hypertension, preeclampsia, postpartum hypertension, pyruvate glutamic transaminase, serum creatinine